Analisis Determinan Pariwisata terhadap Ketimpangan Pendapatan - Resty Aprillia Siska; Hasdi Aimon (Jurnal Kajian Ekonomi dan Pembangunan, 2022)
This study aims to determine the effect of tourism variables on income inequality in West Sumatra. The data used in this study is panel data from 2012 to 2019 taken from the West Sumatra Tourism Office, the Central Statistics Agency (BPS) of West Sumatra. This study uses panel data regression analysis with tourism income, tourism objects, hotels, and tourist visits as independent variables and income inequality as the dependent. The results of this study are (1) tourism income has a positive and significant effect on income inequality, (2) tourism objects have a negative and significant effect on income inequality, (3) hotels have an insignificant negative effect on income inequality, (4) while tourist visits have a positive and significant impact on income inequality. not significant to income inequality in West Sumatra Province in 2012-2019.